Pengembangan Aplikasi Mobile untuk Pelayanan Administrasi Posyandu dengan menggunakan Google Maps Api Geolocation Tagging - Nadia Savitri; Heru Nurwasito (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Today the use of smartphones has become a way of life in almost all walks of life. Mothers are already accustomed to using the Android smartphone to communicate through social media. In general, smartphones are not fully utilized for activities that are productive. This paper discusses the use of Android applications to support the activities of Posyandu (Integrated Service Post). Applications developed can be used to replace the IHC administration system which still manual and conventional. Toddlers data recording process, the immunization schedule, and early childhood development can be done easily and quickly using the Android app on the smartphone. With this application, administrative activities in Posyandu become more efficient and encourages mothers to take advantage of a smartphone with applications more productive.